Synthesis and Crystal Structure of a Novel Square-Hole-Shaped Molecule Mercury(II): C50H48Hg2N2O10S4 - Hu, Xing-Ming; Feng, Xiao-Jun; Pi, Zong-xin; Hu, Jing; Dong, Hua-Ze (Asian Journal of Chemistry, 2013)
A novel complex (C50H48N2O10S4Hg2) was synthesized by pyridyl-pyrimidine dithioethers and Hg(OAc)2 in CH3OH. As the square-hole-shaped molecule, the title compound shows five-coordinate core(HgO3N1S1) which is distorted dipyramid geometry. The crystal is trioclinic, space group P-1 with unit cell parameters: a = 10.10(6)Å, b = 11.14(5)Å, c = 13.41(6)Å, a = 106.3(4)º, b = 103.3(4)º, g = 99.4(4)º, V = 1367(13) Å3, Z = 1, Mr = 1506.46, Dc = 1.830 g/cm3, μ = 5.830 mm-1, F(000) = 736, R = 0.0592, wR = 0.1403 for 6870 reflections with I > 2s(I).